PROFESSIONAL PEDAGOGICAL PHENOMENON AS AN OBJECT OF RESEARCH (Pedagogy of Higher and Secondary Education, 2003)
The definition and structure of a professional pedagogical phenomenon are defined more precisely in the article. On the basis of different points of view the characteristic features of the phenomenon are viewed upon. The pedagogical phenomenon is correlated with practicability, reality and mode of life. A target interrelation between a teacher and a student, means of education and educational environment are singled out in the structure of a pedagogical phenomenon. It is emphasised that it is impossible to get the authentic results of the research without all the components of the pedagogical phenomenon regularity being taken into account.